The effect of using steel fiber in joint mortar on the failure behavior of masonry walls - Yetkin, Musa; Calayır, Yusuf; Alyamaç, Kürşat Esat (My University, 2020)
Masonry structures are the structural system in which the walls are carrier. These structures have a brittle behavior due to the materials that make them up. For this reason, masonry structures/walls exhibit a sudden fracture/collapse behavior under lateral loads such as earthquakes. Due to this behavior, many masonry structures have collapsed from the past to the present under earthquakes and, accordingly, loss of life and property has been experienced. This situation reduced the confidence in masonry structures and thus the interest in constructing masonry structures gradually decreased. In this study, micro steel fibers were used in joint mortar to reduce the brittleness of masonry structures or to delay their sudden collapse. Within the scope of the study, diagonal compression test was applied to the masonry walls produced in stretcher bond type in about 610 x 610 x 90 mm dimensions using solid clay bricks as masonry unit and, reference mortar (mortar without steel fiber reinforce) and micro steel fiber reinforced mortar (mortar with 1%, 2% and 3% steel fiber reinforced) as joint mortar (thickness 20 mm). As a result of the tests, the behavior of masonry walls was compared with each other in terms of crack shapes and collapse patterns. At the end of the study, it was determined that masonry walls formed with mortars containing micro steel fiber behave better than masonry walls formed with reference mortar.
Bildiri - Yayımlanmış
Keywords: Micro steel fiber; Diagonal compression test; Solid clay brick; Masonry structures